Perceived Stress and its Relation with ABO Blood Groups in Medical and Dental Students - Kharel, S.; Raut, B. (Devdaha Medical Journal, 2024)
Introduction: Stress refers to emotional strains or tensions on an individual. Medical education can induce significant psychological stress. Remarkable degree of perceived stress has been found among medical and dental students. The aim of present study was to compare stress levels in medical and dentals students with different ABO blood groups. Method: ABO Blood grouping was done. The Cohen Perceived Stress Scale (CPSS-10), a validated tool, was used to identify levels of stress in young healthy adults. Data collected were analysed using SPSS version 21. Descriptive analysis of levels of perceived stress domains in relation to ABO blood groups was presented as frequency and percentages.Result: The mean CPSS Score among study population was 26.75±4.86 for medical students and 22.38 ±4.22 for dental students. The total no of students were 310. Out of which male and female population was 170 (54.83%) and 140 (45.16%) respectively. The over all prevalence of stress among students (males and females) was 37.09% with moderate to high degree of stress. Difference between males and females were found remarkable. The females were more stressed as compared to males as per CPSS score. Blood group A had high prevalence of stress of 38.26 % followed by blood group B (24.34 %), AB (20 %) and O (17.39 %) respectively.Conclusion: The study showed that students with different blood groups have different levels of stress with high prevalence in blood group A.